PERKAWINAN NGALOR NGULON DITINJAU DARI PERSPEKTIF SYARAT SAHNYA PERKAWINAN MENURUT UNDANG-UNDANG NO 1 TAHUN 1974 DAN HUKUM ISLAM (STUDI KASUS DI DESA TAMBAK REJO KECAMATAN MUNCAR) - Enik Puji Lestari; I Made Yudana; I Wayan Kertih (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2022)
The purpose of this study is to describe the background of the emergence of the tradition of prohibiting ngalor ngulon marriage, to explain how the views of traditional leaders and the community in the Tambak Rejo Village area towards the tradition of prohibiting ngalor ngulon marriage, to analyze the juridical review regarding the legal requirements of marriage according to Law No. 1 of 1974 and Islamic law on the tradition of ngalor ngulon marriage. The method used in this study is a qualitative research method with a phenomenological approach. The results of this study are the village head and each of the traditional leaders have different opinions regarding the background of the ngalor ngulon marriage, the traditional leaders and the community have the same opinion regarding the ngalor ngulon marriage, in Law No. 1 of 1974 especially in CHAPTER II article 6 to 12 there is not a single article that states that ngalor ngulon is prohibited. The three religious leaders in Tambak Rejo Village agree that ngalor ngulon marriages are not regulated in Islamic marriage law, and ngalor ngulon marriages carried out by the perpetrators are still considered legal by the state and religion because they are indeed legal. when carrying out their marriage, they have fulfilled the marriage requirements regulated in Law No. 1 of 1974 and Islamic law, related to the impact of each perpetrator of a ngalor ngulon marriage there is no impact but there is also an impact.